Adsorption of selected azo dyes from aqueous solution onto activated carbon derived from cocoa (theobroma cacao) pod husks. - Aurick Julius V. Wilson, Sophia Maria C. Caparros, Vince Edrick A. De Guzman, Xianne R. Fudalan, Fatima Keith B. Ramos. 4 0 16; 5
ABSTRACT: In this study, activated carbon was prepared from cocoa pod husks via ferric chloride activation for the removal of selected azo dyes. The activation process resulted in a percent yield of 46.84%. The pore volume and surface area of the cocoa pod husk activated carbon (CPHAC) were estimated using methylene blue number (MBN) and iodine number (IN), yielding a result of 171.7 mg g-1 and 577.7 mg g-1, respectively. The surface characteristics of CPHAC were investigated using scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR). Results revealed that CPHAC has a heterogeneous surface with oxygen-containing functional groups. Batch adsorption studies were conducted for the removal of methyl orange (MO), methyl red (MR), Congo red (CR), Eriochrome Black T (EBT), and hydroxynaphthol blue (HNB). The adsorption equilibrium data were fitted to the linear forms of the Langmuir, Freundlich, Dubinin-Radushkevich, and Temkin models. Based on the fin dings of the equilibrium studies, the Freundlich isotherm is the best-fit model for the adsorption of CR and HNB whereas the Temkin, Dubinin-Radushkevich, and Langmuir models are the best for for the adsorption of MO, MR, and EBT, respectively. The kinetics of the adsorption of azo dyes onto CPHAC was also studied. The adsorption kinetic data were fitted to the linear forms of the pseudo-first-order, pseudo-second-order, intraparticle diffusion, and Elovich model. Results from kinetic studies showed that the pseudo-second-order model best describes the adsorption of MR, CR, and EBT onto CPHAC. For the adsorption of MO and HNB, the intraparticle diffusion model best describes the kinetic data.
Undergraduate Thesis:(Bachelor of Science in Chemistry) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2